‘Mama I Can’t Breathe!’: Black/African Women of Faith Groaning for Social Justice and Gender Equality - Parsitau, Damaris (Mission studies, 2021)
This article explores some residual entanglements of colonialism, Christianity, and Afro-western engagement in Africa by using the murder of George Floyd at the hands of police and his cries for “breath” and “mama” as a framework for examining the following. First, we argue that one way in which the repercussions of the transatlantic slave trade remain evident in Africa is the continued police brutality and dehumanization of African citizens. Secondly, with the invocation of “mama,” we consider the plight of African women and colonial/postcolonial Christianity, challenging the African church’s silence on social justice issues, and complicity in the exclusion/oppression of women. We call the church to reckon with its silence, and we offer a corrective towards constructing a theological and missiological response to our cries for breath. While this article is based on African feminist reflections, it invites global participation and indicates wider implications for social and gendered justice.